Chromium Metal Biosorption Using Peanut Shell Adsorbent - Siti Annida; Inayati Inayati; Fera Setiawati (Program studi Teknik Kimia UNS, 2018)
One of the negative effects of the industrial growth is the presence of hazardous waste such as heavy metals. Chromium (VI) is a heavy metal which acts as the pollutant for the environment. Chromium concentration in water can be reduced using some methods. Adsorption is the most favorite method. Some of the biomass can be processed into adsorbent. This work was aimed to produce biosorbent from peanuts shell. The adsorbent was then used to adsorb chromium contented in water. Sodium hydroxide solution 0.5 M was used to activate peanut shell. Produced biosorbent was characterized using Fourier Transform Infrared Spectroscopy. The results showed that optimum condition for chromium adsorption was achieved at 30 minutes contact time with maximum adsorbed chromium of 0.022 mg/g adsorbent. The adsorption mechanism was in a good agreement with Langmuir isotherm.